2002
DOI: 10.1038/nbt0402-381
|View full text |Cite
|
Sign up to set email alerts
|

Engineering N-glycosylation mutations in IL-12 enhances sustained cytotoxic T lymphocyte responses for DNA immunization

Abstract: Interleukin-12 (IL-12), consisting of p40 and p35 subunits, produces both p70 heterodimer and free p40. p70 is essential for the induction of T-helper 1 (Th1) and cytotoxic T-cell (CTL) immunity, whereas p40 inhibits p70-mediated function. Here, we found that mutations introduced into N-glycosylation sites (N220 of murine p40 and N222 of human p40) reduced secretion of p40 but not p70. Co-immunization of N220 mutant mIL-12 gene with hepatitis C virus (HCV) E2 DNA significantly enhanced long-term E2-specific CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 21 publications
1
53
0
Order By: Relevance
“…We previously demonstrated that IL-12N220L DNA, as a prophylactic vaccine, can significantly protect immunized mice against tumor challenge after DNA immunization, compared with wild-type IL-12 DNA immunization. 26 Based on these two studies, we suggest that IL-12N220L DNA could be used as a more effective vaccine than wild-type IL-12 DNA in both therapeutic and prophylactic modes.…”
Section: Dna Vaccines Against Tuberculosis S-j Ha Et Almentioning
confidence: 88%
See 4 more Smart Citations
“…We previously demonstrated that IL-12N220L DNA, as a prophylactic vaccine, can significantly protect immunized mice against tumor challenge after DNA immunization, compared with wild-type IL-12 DNA immunization. 26 Based on these two studies, we suggest that IL-12N220L DNA could be used as a more effective vaccine than wild-type IL-12 DNA in both therapeutic and prophylactic modes.…”
Section: Dna Vaccines Against Tuberculosis S-j Ha Et Almentioning
confidence: 88%
“…26 Briefly, pGX10, DNA vaccine vector, was generated by replacing the ampicillin resistance gene of pTV2 46 with the kanamycin resistance gene. pGX10 is composed of a CMV promoter, TPL, simian virus 40 (SV40) late polyA tail, and an SV40 enhancer, linked in tandem.…”
Section: Il-12n220l Dna Constructsmentioning
confidence: 99%
See 3 more Smart Citations